Assessing Knowledge, Attitude and Practices (KAP) towards COVID19: A Cross-Sectional Study in Kenya (Global Journal of Medical Research, 2020)
Covid-19 is a severe acute respiratory disease that has rapidly spread across the world originated China in December 2019. The main symptoms of a person infected with corona virus are fever, dry cough, shortness of breath, fatigue, dyspnea and myalgia. One of the main tool employed to control the pandemic is providing the community with correct information about the disease. High knowledge, right attitude towards Covid-19 and are adhering to suggested practices is the most effective approach to control community transmission. It is against this background that this study sought to assess Covid-19 knowledge, attitude and practices (KAP) among Kenyans. An online cross-section survey was used to collect data between July 26-31, 2020. From the findings, 9.1 % of the respondents indicated that their relatives, friends or themselves had contracted Covid-19. There is high knowledge of with 83.97 % (82.4,85.54) aware of its symptoms and preventative measures.